Are German tourists environmental chameleons? A micro-econometric analysis of adaptation to climate change - Claudia Schwirplies; Andreas Ziegler (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
This paper empirically analyzes the determinants of individual tourism-related adaptation to climate change, i.e. the stated choice of alternative travel destinations due to increasing temperatures in the future. By examining the tourism sector, our study investigates an industry which was not extensively considered in economic analyses of climate change so far in spite of its worldwide huge economic relevance and strong sensitivity to global warming. Our empirical analysis on the basis of unique representative data from 5370 German tourists first reveals a non-negligible extent of tourism-related adaptation to climate change in the amount of more than 22% of the respondents. Our micro-econometric analysis with binary probit models implies strong positive effects of a high awareness of climate change effects, increasing age as indicator for vulnerability of climate change, as well as a high adaptive capacity (measured by disposable financial resources) on this type of adaptation. The estimation results suggest no single significant effect of a high educational level or a high level of information on adaptation to climate change, but a positive interaction effect (which was, in con-trast to former studies, estimated according to Ai and Norton 2003 and Norton et al. 2004). Our empirical results underline several challenges for the tourism industry and policy makers in order to transform the tourism infrastructure and to diversify holiday offers. They additionally reveal important focus groups of tourists such as (the increasing group of) elderly persons who are crucial for the development of successful future product strategies in the tourism sector.
Keywords: Q54; Q58; 330; Climate change; adaptation; tourism; micro-econometric analysis